Evaluating the Namibia Youth Credit Scheme (NYCS) entrepreneurship programme : the case of the Walvis Bay beneficiaries - Mouton, Daniel A. (Stellenbosch : Stellenbosch University, 2020)
Thesis (MPA)--Stellenbosch University, 2020.